Why develop open source software? The role of non-pecuniary benefits, monetary rewards and open source licence type - Robert M. Sauer (Institute for the Study of Labor (IZA), 2007)
A review of the basic theory of optimal open-source software contributions points to three key factors affecting supply: non-pecuniary benefits, future expected monetary returns, and open-source licence type. This paper argues that existing large-scale software developer surveys are inadequate for measuring the relative importance of these three factors. Moreover, previous econometric studies that collect their own unique datasets generally measure the importance of only one supply factor in isolation. To fill the gap, I specify a dynamic programming model of joint labour supply and open-source contribution decisions that can provide empirical estimates of relative importance within a single unified framework.
Keywords: C61; 330; Software; open-source; labour supply; dynamic programming; Open Source; Programmierung; Arbeitsangebot; Theorie